Non-abstract numerical representations in the IPS: Further support, challenges, and clarifications - Kadosh, R; Walsh, V (2009)
The commentators have raised many pertinent points that allow us to refine and clarify our view. We classify our response comments into seven sections: automaticity; developmental and educational questions; priming; multiple representations or multiple access(?); terminology; methodological advances; and simulated cognition and numerical cognition. We conclude that the default numerical representations are not abstract. © 2009 Cambridge University Press.